2022
DOI: 10.1111/fare.12813
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Ideas. Digital parenting advice: Online guidance regarding children's use of the Internet and social media

Abstract: ObjectiveThis research explores online advice to parents for managing children's Internet and social media use to understand what courses of action are recommended for parents.BackgroundParents often play a protectionist role in parenting, including trying to limit their children's Internet use to reduce harms. However, little is known about the advice parents are provided about how to make these decisions.MethodsWe conducted a content analysis of 73 websites offering advice to parents on guiding their childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Algunos estudios anteriores realizados en muestras de adolescentes y jóvenes van en esta misma línea (Cebollero-Salinas et al, 2021;Sasson y Mesch, 2016;Song et al, 2020). Una posible explicación a este resultado podría deberse a que el tipo de asesoramiento al que le dan más importancia en los hogares, independientemente de la edad, se centra en temas de privacidad y de seguridad (Harris y Jacobs, 2022). De ser así, como los chicos cuando están en Internet dedican más tiempo que las chicas a jugar a videojuegos (Díaz-López et al, 2020;Su et al, 2020), podría suceder que las familias consideraran innecesario el acompañamiento a sus hijos mientras están jugando.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Algunos estudios anteriores realizados en muestras de adolescentes y jóvenes van en esta misma línea (Cebollero-Salinas et al, 2021;Sasson y Mesch, 2016;Song et al, 2020). Una posible explicación a este resultado podría deberse a que el tipo de asesoramiento al que le dan más importancia en los hogares, independientemente de la edad, se centra en temas de privacidad y de seguridad (Harris y Jacobs, 2022). De ser así, como los chicos cuando están en Internet dedican más tiempo que las chicas a jugar a videojuegos (Díaz-López et al, 2020;Su et al, 2020), podría suceder que las familias consideraran innecesario el acompañamiento a sus hijos mientras están jugando.…”
Section: Discussionunclassified
“…Por el contrario, la ausencia de supervisión parental o el uso inadecuado por parte de los padres o tutores afecta negativamente a cómo la utilizan sus hijos (Benedetto e Ingrassia, 2020). Por otro lado, los estudios indican que el tipo de asesoramiento que suelen dar a los hogares tiende más bien a centrarse más en proteger a los niños en temas de privacidad y seguridad que en enseñarles a utilizar la tecnología adecuadamente en su beneficio (Harris y Jacobs, 2022). En cualquier caso, la supervisión familiar resulta un factor protector de riesgos en línea como del uso excesivo de los smartphones (Chang et al, 2019) y del uso problemático de Internet, especialmente en los preadolescentes y las chicas (Cebollero-Salinas et al, 2021).…”
Section: La Relevancia De La Supervisión Familiar En El Uso De Internetunclassified
“…Excessive control or excessive laxity do not reinforce children's positive activities on the Internet; therefore, a parenting style focused on support, teaching proper Internet use, and applying appropriate rules ultimately provides greater benefits to the child or adolescent and their digital growth (i.e., the impact of digital technologies on their personal development; Sasson & Mesch, 2016; Song et al 2020; Valcke et al, 2010). However, Harris and Jacobs (2023) found that the sort of advice generally given to parents tends to focus much more on protecting children (privacy, safety, monitoring) than on teaching them how to navigate social media platforms for their benefit.…”
Section: Xxxfamily Supervisionmentioning
confidence: 99%